(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
As our nation’s bridge infrastructure has aged the need for effective methods of structural health monitoring (SHM) has become increasingly important. Bridge testing has evolved considerably over the past few decades with the advent of small, versatile, and economic sensors and data acquisition on equipment. Today, single‐day bridge tests can be economically conducted, and it is feasible to install a permanent SHM system that will monitor the performance of a bridge.